2016
DOI: 10.1007/s00417-016-3416-9
|View full text |Cite
|
Sign up to set email alerts
|

Variability of panretinal photocoagulation lesions across physicians and patients. Quantification of diameter and intensity variation

Abstract: In this study, the treated area of retina varied by up to a factor of 1.61 = 2.59 for a given spot number. As clinical efficacy depends on the treated area, which is a function of lesion number by area per lesion, our results implicate poor control of the overall treatment effect if treatments are administered according to lesion number or spacing alone. Better ways of laser effect control should be sought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…A report indicated that PRP performed by the short-pulse laser is less effective than that performed by the conventional argon laser in regression of neovascularization or incidence of vitreous hemorrhage within 6 months after treatment when the same number of spots was applied [ 5 ]. It is possible to deduce that the total area of PRP scars in the argon-treated patient exceeds that of the patient who underwent the short-pulse laser [ 10 ], and we should also consider the variability of photocoagulation lesions between physicians and patients [ 24 ], although there were no differences in expansion rates among operators in this study. Therefore, it is important for an operator to reconsider the settings of treatment parameters when using short-pulse laser therapy for serious retinal diseases such as high-risk PDR [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…A report indicated that PRP performed by the short-pulse laser is less effective than that performed by the conventional argon laser in regression of neovascularization or incidence of vitreous hemorrhage within 6 months after treatment when the same number of spots was applied [ 5 ]. It is possible to deduce that the total area of PRP scars in the argon-treated patient exceeds that of the patient who underwent the short-pulse laser [ 10 ], and we should also consider the variability of photocoagulation lesions between physicians and patients [ 24 ], although there were no differences in expansion rates among operators in this study. Therefore, it is important for an operator to reconsider the settings of treatment parameters when using short-pulse laser therapy for serious retinal diseases such as high-risk PDR [ 5 ].…”
Section: Discussionmentioning
confidence: 99%